Novel biochemical predictors of unfavorable prognosis for stable coronary disease - Cacko, Andrzej (Medicine (Baltimore), 2018)
Successful risk stratification is necessary for optimum management of patients after acute coronary syndrome (ACS). The aim of the study was to evaluate the role of novel biochemical markers in the prediction of adverse cardiovascular events in stable patients several years after ACS. The study group was randomly selected from all ACS patients treated with reperfusion therapy between 2002 and 2003 at 1st Department of Cardiology, Medical University of Warsaw, Poland. All patients were readmitted to hospital between 2010 and 2011 for clinical and biochemical cardiovascular risk factors assessment and were prospectively observed for 30-months follow-up. The primary endpoint was all-cause death or hospital readmissions due to a cardiovascular condition at 30 months. The secondary endpoint was a composite of all-cause death or hospitalization-related noncardiovascular condition during the follow-up. The study population consisted of 146 patients (mean age 66.6 ± 9.8 years; 60 female). The primary and secondary endpoints occurred in 49 and 65 patients, respectively. Univariate analysis demonstrated that out of 17 analyzed biomarkers only high-sensitive C-reactive protein (hsCRP), Soluble Fms-Like Tyrosine kinase-1 (sFlt-1), and endothelin-1 (ET-1) were significantly associated with primary end-point and N-Terminal pro-B-type natriuretic peptide (NT-proBNP), hsCRP, ET-1, sFlt-1, and procalcitonin (PCT)—with secondary end-point. Multivariate analysis demonstrated that concentration of sFlt-1 was the only independent factor associated with primary end-point (P = .007 and P = .025, respectively), whereas NT-proBNP and hsCRP levels were only associated with secondary end-point (P = .004 and P = .001, respectively). sFlt-1, NT-proBNP, and hsCRP are associated with adverse outcomes in stable patients several years after ACS and may emerge as useful clinical biomarkers to enhance stratify patient's risk.